A Review of the Health Impact of Nicotine Pouches - Radosław Chmiel; Daria Michałka; Natalie Papachristoforou; Zuzanna Gałuszka; Monika Makar; Tomasz Bartuś; Natalia Tekiela; Emilia Bąk; Justyna Głowacka; Aleksandra Kocjan (Quality in Sport)
Introduction and Purpose of Research